A SCR denitration catalyst hardening liquid and its preparation method and application

By using SCR denitrification catalyst hardening liquid composed of pseudothic aluminite, the problem of decreasing activity after catalyst hardening is solved, the dual improvement of catalyst strength and activity is achieved, the service life is extended and the efficient denitrification performance is maintained.

CN118719168BActive Publication Date: 2025-04-04TIANHE BAODING ENVIRONMENTAL ENG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410791597.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-04-04
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

While the existing SCR denitrification catalyst hardening fluid increases the strength of the catalyst, it will lead to a decrease in the activity of the catalyst and affect the denitrification efficiency.

Method used

A hardening liquid consisting of phthalite, aluminum sulphate octadecanoate, phosphoric acid, monoethanolamine and ammonium metavanadate is used to ensure that the hardness and activity of the catalyst are simultaneously improved through specific formula ratios and preparation methods.

Benefits of technology

The hardening liquid can significantly improve the catalyst's wear resistance and extend its service life, while maintaining the denitrification activity of the catalyst, ensuring stable performance in high temperature and humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118719168B_ABST
    Figure CN118719168B_ABST
Patent Text Reader

Abstract

The invention discloses a SCR denitration catalyst hardening liquid and a preparation method and application thereof, and relates to the technical field of flue gas denitration. The SCR denitration catalyst hardening liquid of the invention comprises the following raw material components in percentage by weight: 10-20wt.% of pseudo-boehmite, 20-30wt.% of aluminum sulfate 18hydrate, 5-10wt.% of phosphoric acid, 2-4wt.% of monoethanolamine, 1-2wt.% of ammonium metavanadate and a water balance. The SCR denitration catalyst hardening liquid of the invention can improve the hardness of the SCR denitration catalyst end, reduce the degree of wear of the SCR denitration catalyst during use, extend the service life of the SCR denitration catalyst, and at the same time, while ensuring the hardness of the catalyst end, do not affect the denitration activity of the catalyst hardened end. The SCR denitration catalyst hardening liquid of the invention has the characteristics of simple preparation method and convenient use, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flue gas denitration, and in particular to a SCR denitration catalyst hardening liquid and a preparation method and application thereof. Background Art

[0002] Nitrogen oxides are one of the major sources of atmospheric pollution. Human production and life will emit nitrogen oxides into the environment, such as coal-burning heating and automobile exhaust. Nitrogen oxides are a serious environmental pollution, mainly because under certain conditions, nitrogen oxides and hydrocarbons form photochemical smog, which damages the atmospheric environment, endangers human health, and forms acid rain. Most nitrogen oxides come from the combustion process of fossil fuels, such as thermal power generation, steel sintering, garbage incineration, glass kilns, cement kilns, etc.

[0003] At present, flue gas denitrification generally adopts SCR denitrification technology. SCR denitrification technology is a selective catalytic reduction technology. By spraying amino reducing agent into the flue gas upstream of the catalyst, the NOx in the flue gas is converted into nitrogen and water through the catalyst.

[0004] In general, the main components of SCR denitration catalysts are titanium oxide and silicon oxide, and the active components are vanadium, tungsten, molybdenum, etc. Honeycomb SCR denitration catalysts are currently more commonly used catalysts. Due to the composition and manufacturing process, the strength of the catalyst is a more important performance indicator, generally for compressive strength and wear rate tests. The wear rate test refers to the degree of wear of the windward end of the honeycomb catalyst under flue gas scouring. In order to improve the hardness of the end of the honeycomb catalyst and improve the ability of the catalyst to resist flue gas scouring, it is necessary to use a hardening liquid to harden the catalyst end. At present, the more common catalyst hardening liquid is aluminum dihydrogen phosphate. This is because aluminum dihydrogen phosphate has a certain viscosity and bonding effect, and produces aluminum pyrophosphate under high temperature conditions, and has a certain high temperature resistance. This catalyst hardening liquid has a greater influence on the activity of the catalyst, and the catalyst end immersed in this curing liquid will lose a certain denitration activity.

[0005] The operating environment of the honeycomb denitrification catalyst is high temperature, with a certain humidity, and dust in the flue gas. The design life of the catalyst is generally 3 years. In this working environment, the windward end (curing end) of the catalyst is required to have strong resistance to high temperature, high humidity, and flue gas wear, which places high demands on the catalyst hardening liquid. The general catalyst hardening liquid chooses to sacrifice the catalyst activity to increase the catalyst strength. This is because these curing liquids generally adhere to the curing end surface by impregnation, blocking the catalyst pore structure, resulting in a decrease in specific surface area and a decrease in denitrification activity.

[0006] In order to solve the above problems, it is necessary to develop a hardening liquid that improves the catalyst strength without affecting the catalyst activity. Summary of the invention

[0007] The purpose of the present invention is to provide a SCR honeycomb denitration catalyst hardening liquid and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art, and to improve the strength of the denitration catalyst without affecting the activity of the catalyst.

[0008] To achieve the above object, the present invention provides the following solutions:

[0009] One of the technical solutions of the present invention is to provide a SCR denitration catalyst hardening liquid, the mass percentage of the raw material components is as follows:

[0010] Pseudo-boehmite 10-20wt.%, aluminum sulfate 18hydrate 20-30wt.%, phosphoric acid 5-10wt.%, monoethanolamine 2-4wt.%, ammonium metavanadate 1-2wt.% and the balance water.

[0011] In the present invention, the pseudo-boehmite contains alumina, which has good peptization performance and strong bonding properties, and is a carrier for the active component to attach. More specifically, in the pseudo-boehmite, Fe2O3≤0.03%, Na2O≤0.10%, LOI (loss onignition)≤35%, peptization index≥95%, alumina trihydrate≤5%, pore volume≥0.3mL / g, and specific surface area≥200m 2 / g.

[0012] Aluminum sulfate 18hydrate (Al2(SO4)3·18H2O) mainly plays the role of structural reinforcement. The ionic bond formed is relatively stable. It forms aluminum pyrophosphate with phosphoric acid under the action of heat, which enhances the structural strength and can improve the catalyst's resistance to high temperature and moisture.

[0013] Phosphoric acid (H3PO4) is mainly used to provide an acidic environment, which is conducive to the dissolution of pseudo-boehmite, and reacts with the aluminum element in the solution under thermal action to produce aluminum pyrophosphate, thereby improving the hardening effect.

[0014] Ammonium metavanadate (NH4VO3), as an active component, is used to maintain the activity of the curing end.

[0015] Monoethanolamine (C2H7NO), as a co-solvent, is mainly used to dissolve ammonium metavanadate.

[0016] The second technical solution of the present invention is to provide a method for preparing the above-mentioned SCR denitration catalyst hardening liquid, which specifically includes the following steps:

[0017] Pseudo-boehmite, aluminum sulfate 18hydrate and phosphoric acid are mixed and stirred uniformly with a part of the formula amount of water (preferably 4 / 5 of the formula amount) at 50-60° C. to obtain solution A;

[0018] Mix ammonium metavanadate, monoethanolamine and the remaining amount of water (preferably 1 / 5 of the amount) at 50-60° C., cool naturally to room temperature, and then adjust the pH value to 6-7 to obtain solution B;

[0019] The solution B is mixed with the solution A to obtain the SCR denitration catalyst hardening solution.

[0020] The impregnation treatment of the catalyst with the hardening liquid can affect the surface and pore structure of the catalyst, thereby affecting the activity of the catalyst.

[0021] The commonly used SCR catalyst curing liquid is aluminum dihydrogen phosphate, which is prepared by dissolving phosphoric acid and aluminum sulfate-containing aluminum salts in water. Although this type of curing liquid can achieve a good curing effect, the activity of the SCR catalyst curing end after impregnation treatment will be significantly reduced, especially the specific surface area of ​​the catalyst will be significantly affected. The present invention solves this problem well, ensuring the strength of the catalyst without reducing the denitration activity of the catalyst.

[0022] In the preparation process of the hardening liquid of the present invention, the aluminum salt in the preparation of solution A is excessive, and reacts with phosphoric acid to form aluminum dihydrogen phosphate, which does not affect the subsequent addition of the active component vanadium. At the same time, solution A has a certain viscosity, which also provides a basis for ensuring the hardening effect; solution B can provide vanadium element, and its separate preparation from solution A can avoid the complexation of vanadium element with phosphoric acid, thereby causing the inactivation of vanadium element.

[0023] The third technical solution of the present invention is to provide the application of the above-mentioned SCR denitration catalyst curing liquid in the curing of the SCR denitration catalyst, more preferably the SCR honeycomb denitration catalyst.

[0024] As a further preference of the present invention, the SCR denitration catalyst can be selected as a catalyst whose main components are titanium, silicon, aluminum, vanadium, tungsten, and molybdenum. This type of catalyst has a porous structure. After the impregnation is completed and contacted, it is dehydrated and decomposed when heated (aluminum dihydrogen phosphate is dehydrated and decomposed when heated to convert into aluminum phosphate salts. This process can be carried out at room temperature. The application environment temperature of the catalyst is relatively high, which will further accelerate the process). The generated aluminum phosphate has a very stable and tight chemical bond, which achieves a firm adhesion of the structure and improves the hardness. The aluminum contained in the pseudo-boehmite and an appropriate amount of phosphoric acid generate a phosphorus aluminum molecular sieve under the action of heat, which provides a carrier attachment point for the vanadium element, and can make up for the denitration activity after the solidification end.

[0025] As a further preferred embodiment of the present invention, the application process includes the following steps: immersing the SCR denitration catalyst in the SCR denitration catalyst hardening liquid, and drying.

[0026] As a further preference of the present invention, the immersion temperature is room temperature, and the drying temperature is room temperature.

[0027] A fourth technical solution of the present invention is to provide an SCR denitration catalyst, one end of which is treated by immersion and hardening in the SCR denitration catalyst hardening liquid.

[0028] The present invention discloses the following technical effects:

[0029] 1. The SCR denitration catalyst hardening liquid of the present invention can improve the hardness of the SCR denitration catalyst end, reduce the degree of wear of the SCR denitration catalyst during use, and extend the service life of the SCR denitration catalyst.

[0030] 2. After the end of the existing SCR denitration catalyst is hardened, the denitration activity will be reduced. The SCR denitration catalyst hardening liquid of the present invention can ensure the hardness of the catalyst end without affecting the denitration activity of the catalyst hardened end.

[0031] 3. The application environment of SCR denitration catalyst is mostly high temperature and contains a certain amount of moisture. The SCR denitration catalyst treated with the hardening liquid of the present invention has a certain ability to resist high temperature and moisture.

[0032] 4. The SCR denitration catalyst hardening liquid of the present invention has a simple preparation method, is easy to use, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The SCR honeycomb denitration catalyst having a solidified end (hardened end) is obtained by impregnating the SCR honeycomb denitration catalyst with the denitration catalyst hardening liquid prepared in Example 1 of the present invention; wherein 1 is the hardened end and 2 is the non-hardened end. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] The raw material components of the denitration catalyst hardening liquid of the present invention are as follows:

[0041] Table 1

[0042] Components Quality content Pseudoboehmite 10-20wt.% Aluminum sulfate 18hydrate 20-30wt.% Phosphoric acid 5-10wt.% Monoethanolamine 2-4wt.% Ammonium metavanadate 1-2%wt.% Deionized water margin

[0043] The raw material compositions of the denitration catalyst hardening liquid of Examples 1-4 and Comparative Examples 1-4 of the present invention are as follows:

[0044] Table 2

[0045]

[0046] The preparation of the denitration catalyst hardening solution of Examples 1-4 of the present invention is as follows:

[0047] (1) Pseudo-boehmite and aluminum sulfate 18hydrate are added to deionized water in a ratio of 4 / 5 of the formula, phosphoric acid is slowly added under stirring, the temperature is raised to 60° C., and the solution is stirred and dissolved to obtain solution A;

[0048] (2) adding ammonium metavanadate and monoethanolamine to 1 / 5 of the formula amount of deionized water, heating to 60° C., stirring until fully dissolved, naturally cooling to room temperature, and adjusting the pH value to 7 with concentrated sulfuric acid to obtain solution B;

[0049] (3) Solution B was added to solution A under stirring and stirred for 30 minutes to obtain a denitration catalyst hardening solution.

[0050] The preparation of the denitration catalyst hardening liquid of Comparative Example 1 of the present invention is as follows:

[0051] (1) adding aluminum sulfate 18hydrate to deionized water in an amount of 4 / 5 of the formula, slowly adding phosphoric acid under stirring, heating to 60° C., stirring and dissolving to obtain solution A;

[0052] (2) adding ammonium metavanadate and monoethanolamine to 1 / 5 of the formula amount of deionized water, heating to 60° C., stirring until fully dissolved, naturally cooling to room temperature, and adjusting the pH value to 7 with concentrated sulfuric acid to obtain solution B;

[0053] (3) Solution B was added to solution A under stirring and stirred for 30 minutes to obtain a denitration catalyst hardening solution.

[0054] The preparation of the denitration catalyst hardening liquid of Comparative Example 2 of the present invention is as follows:

[0055] (1) Pseudo-boehmite was added to deionized water in an amount of 4 / 5 of the formula, phosphoric acid was slowly added under stirring, the temperature was raised to 60° C., and solution A was obtained by stirring and dissolving;

[0056] (2) adding ammonium metavanadate and monoethanolamine to 1 / 5 of the formula amount of deionized water, heating to 60° C., stirring until fully dissolved, naturally cooling to room temperature, and adjusting the pH value to 7 with concentrated sulfuric acid to obtain solution B;

[0057] (3) Solution B was added to solution A under stirring and stirred for 30 minutes to obtain a denitration catalyst hardening solution.

[0058] The preparation of the denitration catalyst hardening liquid of Comparative Example 3 of the present invention is as follows:

[0059] (1) Pseudo-boehmite and aluminum sulfate 18hydrate are added into deionized water of 4 / 5 of the formula amount, the temperature is raised to 60° C., and stirred to dissolve to obtain solution A;

[0060] (2) adding ammonium metavanadate and monoethanolamine to 1 / 5 of the formula amount of deionized water, heating to 60° C., stirring until fully dissolved, naturally cooling to room temperature, and adjusting the pH value to 7 with concentrated sulfuric acid to obtain solution B;

[0061] (3) Solution B was added to solution A under stirring and stirred for 30 minutes to obtain a denitration catalyst hardening solution.

[0062] The preparation of the denitration catalyst hardening liquid of Comparative Example 4 of the present invention is as follows:

[0063] (1) Pseudo-boehmite and aluminum sulfate 18hydrate are added to deionized water in a ratio of 4 / 5 of the formula, phosphoric acid is slowly added under stirring, the temperature is raised to 60° C., and the solution is stirred and dissolved to obtain solution A;

[0064] (2) adding monoethanolamine to 1 / 5 of the formula amount of deionized water, heating to 60° C., stirring until fully dissolved, cooling naturally to room temperature, and adjusting the pH value to 7 with concentrated sulfuric acid to obtain solution B;

[0065] (3) Solution B was added to solution A under stirring and stirred for 30 minutes to obtain a denitration catalyst hardening solution.

[0066] Effect verification example:

[0067] The SCR honeycomb denitrification catalyst was impregnated with the denitrification catalyst hardening liquid prepared in Examples 1-4 and Comparative Examples 1-4 respectively (catalyst specification 15*15*15cm, number of holes 13*13, pitch 11.33mm, hardening liquid immersion length 5cm, immersion time 5s). After the impregnation was completed, it was taken out and naturally dried to obtain a honeycomb SCR denitrification catalyst with a cured end.

[0068] The main component contents of the SCR honeycomb denitrification catalyst used are shown in Table 3:

[0069] Table 3

[0070]

[0071]

[0072] Figure 1 A honeycomb SCR denitration catalyst with a solidified end (hardened end) is obtained by impregnating the SCR honeycomb denitration catalyst with the denitration catalyst hardening liquid prepared in Example 1, wherein 1 is the hardened end and 2 is the non-hardened end.

[0073] The specific surface areas of the honeycomb SCR denitration catalysts with cured ends prepared in Examples 1-4 and Comparative Examples 1-4 are shown in Table 4, and the wear rates are shown in Table 5.

[0074] Wear rate determination steps: Wrap the test sample with kaolin wool and install it in the sample bin (test equipment sample bin), with the hardened end of the sample as the windward side, and keep the outer wall of the sample and the bin wall completely sealed with kaolin wool, and use air and abrasives to flow completely through the channel of the sample. The test adjusted the wind speed of the catalyst channel to 14.5m / s±0.5m / s, the diameter of the air duct before entering the sample bin was 65mm, and the abrasive was dry quartz sand of 0.300mm-0.425mm, with a concentration of 50g / m 3 ±5g / m 3 , stop after 2 hours, take out the sample, put it in an oven, dry it at 105℃±2℃ for 2 hours, cool it naturally to room temperature, and weigh it to an accuracy of 0.01g. The sample that has not been immersed in the hardening solution is used as a comparison sample (blank sample).

[0075] Wear rate calculation steps: The wear rate ζ of the catalyst, expressed in percentage per kilogram (% / kg), is calculated according to the following formula:

[0076]

[0077] Where:

[0078] m2——the value of the mass of the sample after the test, in grams (g);

[0079] m1——the value of the sample mass before the test, in grams (g);

[0080] m3——the value of the mass of the comparison sample before the test, in grams (g);

[0081] m4——the value of the mass of the comparison sample after the test, in grams (g);

[0082] m——the numerical value of the mass of the abrasive, in kilograms (kg).

[0083] Table 4 Specific surface area of ​​samples

[0084]

[0085] Table 5. Relationship between wear rate of cured end of samples

[0086]

[0087]

[0088] The prepared honeycomb SCR denitration catalyst with a solidified end is placed in a flue gas temperature of 250-400°C and an inlet NO X 500mg / Nm 3 , 5v.%O2, 30mg / Nm 3 SO2, 30mg / Nm3 The molar ratio of H2O and ammonia nitrogen is 1, 6000h -1 The denitrification efficiency was measured at an air velocity of . The denitrification efficiency is shown in Table 6.

[0089] Table 6 Denitrification efficiency relationship

[0090]

[0091] The catalyst hardening liquid of the present invention mainly functions to improve the wear resistance of the catalyst curing end, reduce the wear rate, and ensure that the denitration performance of the catalyst curing end is not reduced. The main focus is on the wear rate of the catalyst. The lower the wear rate, the better the hardening effect of the catalyst.

[0092] As can be seen from Table 4, the addition of phosphoric acid will reduce the specific surface area of ​​the catalyst, while the addition of pseudo-boehmite will increase the specific surface area of ​​the catalyst. Generally, due to the impregnation and covering of the hardening liquid, the specific surface area of ​​the solidified end of the catalyst will be reduced to a certain extent. This is because the impregnated material enters the interior of the catalyst to cause pore blockage, thereby reducing the specific surface area and denitration capacity. Compared with the traditional hardening liquid, the hardening liquid in the present invention has less effect on the specific surface area.

[0093] From the relationship of curing end wear rate in Table 5, it can be seen that after impregnation, the wear rates of the catalysts of Examples 1-4 and Comparative Examples 1-4 are reduced, and the lower the wear rate, the higher the wear resistance of the catalyst. Among them, the wear rates of Examples 1-4 are all lower than those of the corresponding Comparative Examples 1-4, because the aluminum, phosphorus and other elements in the curing liquid are dehydrated and decomposed by heat to generate aluminum phosphate with a strong bonding degree and stable chemical bonds, thereby increasing the strength of the catalyst curing end.

[0094] It can be seen from the denitration efficiency table in Table 6 that the purpose of the hardening liquid of the present invention is to ensure that the denitration activity does not decrease after the impregnation is completed. Under normal circumstances, the activity of the solidified end of the impregnated hardening liquid will decrease. The reason is that the hardening liquid adheres to the catalyst surface, destroys the active sites on the catalyst surface, and reduces the specific surface area. After the hardening liquid of the present invention is impregnated, the denitration activity is slightly improved.

[0095] The test data show that the higher the phosphoric acid content, the more it has a certain inhibitory effect on the denitrification activity of the catalyst. The reason may be that the active sites of the catalyst are bound by phosphorus elements, and the activity is passivated. As can be seen from Table 5, appropriate phosphorus elements help reduce the wear rate of the catalyst, which is the main reason for controlling the amount of phosphoric acid added in the present invention. At the same time, pseudo-boehmite contains a certain amount of aluminum elements, which form phosphorus-aluminum molecular sieves with phosphoric acid, which helps to increase the surface area and provide new attachment points for the active component vanadium element. This is also the reason why the catalyst activity after being immersed in the hardening liquid is slightly higher than the denitrification activity of the blank sample. Pseudo-boehmite, phosphoric acid and other components need to be controlled in appropriate proportions. The lack of a certain component alone or the inappropriate proportion of the components cannot make the hardening liquid have the effect of hardening the catalyst to improve the wear resistance, nor can the hardening liquid have the function of supplementing the activity of the catalyst curing end.

[0096] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A SCR denitration catalyst curing liquid, characterized in that: The mass percentage of raw material components is as follows: 10-20wt.% of pseudo-boehmite, 20-30wt.% of aluminum sulfate 18hydrate, 5-10wt.% of phosphoric acid, 2-4wt.% of monoethanolamine, 1-2wt.% of ammonium metavanadate and the balance of water; The method for preparing the SCR denitration catalyst hardening liquid comprises the following steps: Pseudo-boehmite, aluminum sulfate 18hydrate and phosphoric acid are mixed with a portion of the formula amount of water at 50-60° C. to obtain solution A; Mix ammonium metavanadate, monoethanolamine and the remaining amount of water at 50-60°C, cool to room temperature and adjust the pH value of the system to 6-7 to obtain solution B; The solution B is mixed with the solution A to obtain the SCR denitration catalyst hardening solution.

2. Use of the SCR denitration catalyst hardening liquid as claimed in claim 1 in the hardening of the SCR denitration catalyst.

3. The use according to claim 2, characterized in that The application process comprises the following steps: immersing the SCR denitration catalyst in the SCR denitration catalyst hardening liquid according to claim 1, and drying.

4. The use according to claim 3, characterized in that The immersion temperature is room temperature; the drying temperature is room temperature.

5. An SCR denitration catalyst, characterized in that: The SCR denitration catalyst is impregnated with the SCR denitration catalyst hardening liquid according to claim 1.

Citation Information

Patent Citations

  • Hardening liquid for denitration catalyst module and hardening method

    CN105665032A

  • Method for improving mechanical strength of integral honeycomb type denitration catalyst

    CN114130432A